Critical issues in urban technologies for sustainable development: the case of water infrastructure in Mexico city - Zoreda-Lozano, Juan J.; Castaneda, Victor (1998)
This paper presents a general approach to the structural links between urban technologies for water use and sustainable development in Mexico city. These links belong to the public domain and are sufficiently generalizable so as to be expanded and modified to suit other technologies in similar contexts. They offer a convenient backdrop against which to meaningfully address critical technological issues that affect the performance of urban settlements as well as their biophysical environments. - Reproduced
Keywords: Water supply